2016
DOI: 10.1158/1055-9965.epi-15-1291
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk for Noncervical Anogenital Cancer in Women with Previously Diagnosed High-Grade Cervical Intraepithelial Neoplasia: A Danish Nationwide Cohort Study

Abstract: Background: High-risk human papillomavirus (HPV) is essential for developing high-grade cervical intraepithelial neoplasia (CIN2 and CIN3) and has also been associated with noncervical anogenital cancers. However, limited knowledge exists about the long-term risk for anal, vulvar, and vaginal cancer following CIN2 or CIN3 diagnosis.Methods: In a nationwide cohort study, we followed nearly 2.8 million women born in who were recorded as living in Denmark between January 1, 1978 and December 31, 2012. The cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
2
25
0
2
Order By: Relevance
“…High grade lesions are characterized as cervical intraepithelial neoplasia(CIN) 2 and -3, and considered intermediate stages in the cancer progression, often developing within 5 years of infection with these high-risk HPV types [2]. Women with high-grade CIN have a long-term risk of not only cervical cancer, but also anal, vulvar, and vaginal cancers, when compared to the general population [3][4][5]. Additionally, a few studies have exposed an association between high-grade CIN and head and neck cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…High grade lesions are characterized as cervical intraepithelial neoplasia(CIN) 2 and -3, and considered intermediate stages in the cancer progression, often developing within 5 years of infection with these high-risk HPV types [2]. Women with high-grade CIN have a long-term risk of not only cervical cancer, but also anal, vulvar, and vaginal cancers, when compared to the general population [3][4][5]. Additionally, a few studies have exposed an association between high-grade CIN and head and neck cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Testing women with a history of cervical cancer for anal HPV and dysplasia clearly meets established appropriateness criteria for a potentially viable screening program [33] . Patients with a history of cervical neoplasia have been recently proven to represent a population at risk for persistent infection with oncogenic subtypes of HPV [34] . Similar to cervical cytologic testing [35] , simple anal sampling techniques can be used to simultaneously determine the presence of high risk HPV subtypes and to evaluate for evidence of dysplasia [36] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sand et al 7 reviewed years 1978-2012 from a Danish registry study and identified 125 incident anal cancers from 104,155 women with CIN3 and 32 from 52,135 women with CIN2. The mean age of diagnosis of women with CIN3 and CIN2 was the same at 34 years.…”
Section: Cin3 and Cervical Cancer: Risk Factors For Anal Cancermentioning
confidence: 99%
“…In particular, the increased risk of anal cancer began at the time of CIN3 diagnosis (regardless of the age at diagnosis), increased to 6 per 100,000 at ages 40-49 to 24 per 100,000 from age 60 and older; in this cohort, the increased risk of anal cancer continued for over 25 years following CIN2,3 diagnosis. 7 …”
Section: Cin3 and Cervical Cancer: Risk Factors For Anal Cancermentioning
confidence: 99%